FREQUENCY OF EXCLUSIVE BREASTFEEDING IN INFANTS PRESENTING TO KHYBER TEACHING HOSPITAL, PESHAWAR - Idrees, Saba; Shaid, Fazlina; Idrees, Sana (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine the frequency of exclusive breastfeeding in infants visiting a tertiary care hospital, Peshawar. Methodology: This cross sectional study was conducted in pediatric outpatient department (OPD) of Khyber Teaching Hospital Peshawar from July 2018 to December 2018. A total of 250 infants aged 0-6 months of either gender, brought to OPD for various illnesses were enrolled. Demographic characteristics of all patients were recorded. History of breast feeding was obtained and recorded in a pre designed proforma. Results: Our study showed that among 250 infants, mean age was 4 ± 1.94 months. Sixty four percent babies were males and 35.6% babies were females. The frequency of exclusive breast feeding was 61.2% in these infants. Conclusion: Our study concluded that the frequency of exclusive breastfed infants was 61.2 %.